Autonomic nervous system, training load and performance in competitive swimming in a pair of monozygotic twin sisters - Garet, M.; Tournaire, N.; Roche, F.; Laurent, R.; Lacour, J. R.; Barthelemy, J. C.; Pichot, V. (First international symposium sciences and practices in swimming, 2006)
The interdependence between ANS activity, training load and performance as previously described in competitive swimmers is a valuable issue in the control and optimization of training. Not only the relative individual evolution of ANS activity but also the absolute amount of autonomic activity seems determinant of performance. The present study performed in a pair of monozygotic twin sisters further strengthen the individual relationship between ANS activity and performance as the many anthropometrical, biological and physiological factors usually interfering in these relationships are naturally taken into account. Both the absolute amount of ANS activity, systematically greater in one sister, along with its relative evolution are determinant of performance, better for the same sister, and performance evolution (similar in both sisters). Further studies should address this issue in a larger cohort of monozygotic twins.